2022
DOI: 10.3389/fpsyg.2022.1023724
|View full text |Cite
|
Sign up to set email alerts
|

Perceived overall injustice and organizational deviance—Mediating effect of anger and moderating effect of moral disengagement

Abstract: IntroductionThis study is dedicated to exploring the influence of perceived overall injustice on employee anger and deviant behavior. Based on fairness heuristic theory and cognitive appraisal theory of emotion, a model was developed to investigate the relationship between perceived overall injustice, anger and organizational deviance. Based on social cognitive theory, the moderating role of moral disengagement was proposed.MethodsThe data were collected from three Chinese manufacturing corporations with a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…Research has shown that angry individuals who suffer from unfair treatment (such as intentional insults and injuries), goal interference and negative interpersonal events tend to adopt negative opinions toward the organization, leading to strong confrontational and aggressive behavior (Chow et al, 2008;Leary et al, 2006). For example, angry individuals achieve psychological balance by engaging in organizational deviance (Qin and Zhang, 2022) and counterproductive behavior (Zhu and Zhang, 2021). In addition, anger is closely related to aggressive behavior, withdrawal behavior and theft (Chen and Spector, 1992) and can also increase the tendency to abuse others (Mawritz et al, 2014).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that angry individuals who suffer from unfair treatment (such as intentional insults and injuries), goal interference and negative interpersonal events tend to adopt negative opinions toward the organization, leading to strong confrontational and aggressive behavior (Chow et al, 2008;Leary et al, 2006). For example, angry individuals achieve psychological balance by engaging in organizational deviance (Qin and Zhang, 2022) and counterproductive behavior (Zhu and Zhang, 2021). In addition, anger is closely related to aggressive behavior, withdrawal behavior and theft (Chen and Spector, 1992) and can also increase the tendency to abuse others (Mawritz et al, 2014).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Research has shown that individuals have basic needs for belonging and connection with others (Leary et al, 2006). Due to the traditional Chinese circle culture and collectivist culture, individuals have more pronounced needs for harmonious interpersonal relationships and belonging (Qin and Zhang, 2022;Zhao et al, 2016). Becoming a member of a circle can result in a sense of belonging, identity and self-worth (Turner, 1975) and even offer the opportunity for the individual to exchange value with other people within the circle (Dienesch and Liden, 1986).…”
Section: Workplace Ostracism and Knowledge Sabotage Behaviormentioning
confidence: 99%
“…POI can be a powerful driver of moral disengagement (MD) among employees (Qin and Zhang, 2022). MD refers to the cognitive processes that enable people to rationalize/justify their injurious/harmful conduct.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, repeated instances of POI and MD can foster a toxic work environment that undermines trust, collaboration and productivity. To prevent POI from negatively affecting employee behavior, businesses must encourage fairness, openness and high ethical standards at work (Qin and Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation